Action Research reflecting the process of a collaborative, multi-theoretical group intervention with foster parents of children affected by childhood trauma - Cahill, Susan Mary (Rhodes University, Faculty of Humanities, Department of Psychology)
Children are received into the Care of the State in the Republic of Ireland due to chronic or acute maltreatment in their families of origin. Maltreatment may include neglect; physical, sexual, or emotional abuse; exposure to domestic violence; or a combination of these. Resulting emotional and behavioural consequences may be challenging to foster parents who might experience stress, secondary trauma, compassion fatigue or burnout, which along with the child's emotional and behavioural difficulties can result in placement breakdown. After reviewing the literature on fostering internationally and in Ireland, this study sought to determine the types and level of stress in a sample of foster parents and the types of challenging emotional and behavioural difficulties of their fostered children. Results revealed that foster parents found fostering stressful; factors included biological parents; organisational issues; and the child's behaviour. According to the foster parents, nearly 60% of the foster children in this sample were showing high levels of emotional and behavioural distress. These difficulties differed according to age and gender. Adolescent Girls and Young Boys (5 "“ 11 years) were reported as having the most difficulties, including symptoms of behavioural and Conduct Disorder (CD). Symptoms associated with CD were reported in at least 40% of every age and gender category of children over five years. Further, this study outlines the development, facilitation and outcomes of a small group psychoeducational-reflective foster parenting Course, involving six separate groups of parents (n=38) each meeting for eight sessions. In this Course, foster children were conceptualised from a bio-psycho-social-ecological viewpoint, utilising theoretical concepts from Prenatal Development, Attachment and Trauma, pertaining to vulnerable children to illustrate the cumulative effects of adversities. Time for discussion and reflection on the material was structured into the Course. This combination of knowledge, practical skills, reflection and support for parents aimed to promote healing relationship-based practices for the child within their foster home. This multi-faceted study was grounded in Community Psychology, using mixed methods to gather data during action research processes, to reflect the different components of an action cycle. Ideas and modifications to the Course based on feedback from the foster parent participants' experiences have been included. It is recommended that the Course be provided to other foster parents and audiences such as social workers, teachers and solicitors. Furthermore, suggestions are made regarding assessment, diagnosis and interventions for foster children and parents, based on a multidisciplinary consultancy model.
Keywords: Foster parents -- Ireland; Foster home care -- Ireland; Attachment theory; Psychic trauma in children; Group psychotherapy; Parenting stress